Integrating Deep Learning Principles into Pesantren Education: A Transformative Model for Meaningful Islamic Learning - Ummu Habibah; Dini Siamika Tito Prayogi (Universitas Nurul Jadid, 2026)
The purpose of this study is to demonstrate that the concept of deep learning has long been inherently realized within the traditional educational practices of pesantren, even before it was formally introduced in modern academic discourse. Pesantren, as the oldest Islamic educational institutions in Indonesia, have developed a holistic learning system that integrates intellectual, spiritual, and social dimensions in a sustainable manner. This research was conducted at Pondok Pesantren Nurul Ulum Cindogo using a qualitative field research approach. Data were collected through in-depth observations, semi-structured interviews, and documentation, involving kyai, ustadz, administrators, and students as key informants. The findings reveal that the fundamental principles of deep learning mindful learning, meaningful learning, and joyful learning are deeply embedded in the daily life and educational practices of the pesantren. Mindful learning is reflected in the development of students’ metacognitive awareness through disciplined study habits, reflective practices, and spiritual internalization. Meaningful learning is realized through instructional methods such as sorogan and the communal living system, which connect theoretical knowledge with authentic life experiences and social responsibility. Meanwhile, joyful learning is manifested in participatory activities such as halaqah and lalaran, fostering active engagement, emotional connection, and intrinsic motivation among students. This study concludes that pesantren education not only aligns with but also predates and exemplifies the principles of deep learning. Therefore, it offers a contextual, holistic, and value-based model that can contribute significantly to the development of contemporary education